Экспериментальное исследование процессов ударного нагружения тонких пластин - Бреславский, Дмитрий Васильевич; Наумов, Иван Владимирович; Онищенко, А. В. (НТУ "ХПИ", 2007)
The paper describes the experimental facilities had been developed in NTU «KhPI» for the modeling of the impact interaction between the pellet and thin rectangular plate. The experimental unit, as well as its components, are described. The example of the experimental unit's working at the testing process is given.
Keywords: информационная измерительная система; поле соленоида; датчики; деформирование пластины; сигнал тензодатчиков; тензорезисторы